Из проблематики духовных ценностей русского православия – „Дневник писателя” эмигранта Б.К. Зайцева - Mianowska, Joanna (Wydawnictwo Naukowe UAM, 2013)
The prose written by a representative of the First Wave of Russian Emigration – B.K. Zaytsev – has been investigated in Poland since the 1980s, and at the beginning of the 21st century we know that there are some academic centers and researchers that have dedicated their work to different aspects of the prose written by the author of ’A Writer’s Diary’. This article examines Zaytsev’s essays devoted to the spiritual values of the Russian Orthodox Church. Their essence is described in Zaytsev’s essays about John of Kronstadt or the Optina Hermitage, which is where Russian notables such as N. Gogol, V. Solovyov, K. Leontyev, F. Dostoyevsky or even L. Tolstoy himself came to seek advice. Zaytsev’s essays: ‘The history of the Russian soul’ and ‘One more time about Athos’ are very important as they provide an understanding of the values of the Russian Orthodox Church. In the latter the author contemplates his visit to the monks of Athos reminiscing about their kindness, rectitude and modesty which, according to Zaytsev, ‘calmed his own soul’.
Problematic aspects of the Russian Orthodox Church’s spiritual values – “A Writer’s Diary” by the emigrant B.K. Zaytsev
Z problematyki wartości duchowych rosyjskiego prawosławia – „Dziennik pisarza” emigranta B.K. Zajcewa